Supporting Aging in Communities through University-Community Collaborations (2023)
We are generally unprepared for the precipitated population aging that we are experiencing worldwide. Much of this has to do with a long-standing ageist attitude and, perhaps consequently, a general lack of foresight or attention to the needs of aging populations. This ageism is financially costly and has severe consequences for people’s well-being. According to Levy et al. (2020), ageism costs $63 billion annually in the United States. It is associated with 17 million cases of cardiovascular disease, chronic respiratory disease, musculoskeletal disorders, injuries, diabetes mellitus, treatment of smoking, mental disorders, and non-communicable diseases. Ageism is predicted by age discrimination (a detrimental treatment of older persons), negative age stereotypes (negative beliefs of older persons about older people in general), and negative self-perceptions of aging (negative beliefs of older persons about their aging) (Levy et al., 2020). Ageism is embedded in most of our institutions, including those providing health and social services and in the media, educational, and legal systems. Ageism is a major barrier to enacting effective policies for aging societies (WHO, 2021), including educating our future workforce to meet the needs of an inevitably aging population.